(untitled) (Bodhi Path, 2023)
This paper is an attempt to elucidate the philosophical perspectives on “Aji kan” as the beginning of things, the being of things and the negation of things as the source found in Dainichi kyō (Taishō Vol. 39, No. 1796). As a seed mantra the syllable “A” plays an important role in Buddhism. “A” syllable is rooted in Indian understandings of language and the associations that arise in relation to these. The rumblings of the mind are a cause of perpetual anguish for the human being. Mind is the germinating point of distress, negativity, tentacles, in fact, all the troubles in the present life as well as the life hereafter. Yet, a pertinacious training of the mind offers a possibility of a calm mind. The practice of the Ajikan denotes the letter in script and words in speech. These are the tools in communication with the environment, people, and specifically with oneself. Speech connotes inner thoughts and the breathing helps in transmission. Anger, dissatisfaction, disgust etc. increases the heart rate leading to faster breathing pattern. Thus, affecting the functioning of the mind. Similarly, a change in thought process coupled with peaceful environment and conducive sounds produce a calming effect. Therefore, letters, sound and visible pictures can be used as instruments to be used in controlling the mind. The practice of Ajikan is an ancient practice reflecting the deep insight into functioning of the mind and the interconnection of the letter, sound and visible picture as an illustration. The philosophers have persistently endeavoured to churn the depths of theory and practice to seek solutions to this issue. Their effort resulted in turning to Ajikan as the focal point of rumination.